Engineering materials for biomedical applications - Teoh, Swee Hin (Biomaterials engineering and processing series ;, 2004)
The success of any implant or medical device depends very much on thebiomaterial used. Synthetic materials (such as metals, polymers andcomposites) have made significant contributions to many establishedmedical devices. The aim of this book is to provide a basicunderstanding on the engineering and processing aspects ofbiomaterials used in medical applications.